2005
DOI: 10.1109/tns.2005.860738
|View full text |Cite
|
Sign up to set email alerts
|

Proton damage effects in high performance P-channel CCDs

Abstract: P-channel CCDs with pre-rad imaging characteristics comparable to the best N-channel CCDs have been fabricated and tested. These devices have been subjected to proton damage and display the superior hardness predicted for them.Index Terms-Charge transfer efficiency, displacement damage hardened imagers, P-channel CCDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The results are comparable to other reported values of activation energies of 0.61 eV [15] and 0.63 eV [18]. The measurement suggests that, for the p-channel devices tested, the divacancy is the dominant source of thermally generated dark current pre and post irradiation.…”
Section: Dark Currentsupporting
confidence: 88%
“…The results are comparable to other reported values of activation energies of 0.61 eV [15] and 0.63 eV [18]. The measurement suggests that, for the p-channel devices tested, the divacancy is the dominant source of thermally generated dark current pre and post irradiation.…”
Section: Dark Currentsupporting
confidence: 88%
“…The LBNL p-channel CCDs are fabricated on high-resistivity n-type silicon with boron implanted channels. In the p-channel CCDs, divacancy states are expected to be the dominant hole trap [7]- [9]. It has been predicted that divacancy formation in p-channel CCDs is less favorable than phosphorus-vacancy traps in n-channel CCDs [8], and prior studies have shown improved performance after radiation exposure [7], [10], [11].…”
Section: Ccd Requirementsmentioning
confidence: 99%
“…The increased tolerance to displacement damage of a p-channel CCD was first demonstrated in 1997 2 and since then a number of other studies have demonstrated an improved hardness to radiation induced charge transfer inefficiency (CTI) when compared to n-channel CCDs [3][4][5][6][7] . The improvement has been linked to the number and type of defects formed within the buried channel, 3 and how these defects impact charge transfer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation induced defects which increase CTI in a p-channel CCD have been linked to the divancancy and other traps related to carbon and oxygen interstitials [3][4][5][6][7][8] . As there are less radiation induced defects in a p-channel CCD which have been shown to increase CTI and because they are formed in smaller quantities (the divacancy is a second order defect and boron defects have not 4 been shown to impact CTE) when compared to an n-channel equivalent, p-channel CCDs are more hard to radiation induced CTI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation